Microplots and food security: Encouraging replication studies of policy relevant research - Douglas Kuflick Benjamin Wood; Maria Vasquez (Kiel Institute for the World Economy (IfW), 2017)
Replication research is a valuable, yet often misunderstood, tool for increasing our understanding of promising research findings. In their short paper below the authors discuss their principles for conducting replication research, explain how they picked a candidate study for replication, describe the robustness checks they would conduct in their replication plan, and give an overview of how they would interpret their replication results. The authors also describe some of their lessons learned after working in replication research for over five years.
Keywords: Q18; O13; 330; Replication; food security; research transparency; impact evaluation